THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND EMPLOYEE MPOWERMENT ON EMPLOYEE JOB SATISFACTION IN THE REGIONAL LEGISLATIVES COUNCIL OFFICE IN SOUTHEAST MINAHASA - Gabriella Virginia Lumintang; Willem J. F. A. Tumbuan; Emilia M. Gunawan (Universitas Sam Ratulangi, 2024)
Job satisfaction is an important factor in a company's ability to meet organizational goals and represents a person's feelings toward his work. The purpose of this study is to determine whether emotional intelligence and employee empowerment influence employee job satisfaction in the Regional Legislatives Council Office in Southeast Minahasa. This study used a quantitative approach and Multiple Linear Regression as its analytical tool. The sampling technique of this research is saturation sampling with 40 respondents as samples by using a questionnaire to collect primary data. The results of this study revealed that each of emotional intelligence and employee empowerment partially has a positive and significant effect on employee job satisfaction simultaneously, both emotional intelligence and employee empowerment significantly and positively influence employee job satisfaction. Therefore, a combination of emotional intelligence and employee empowerment contribute to higher job satisfaction. Keywords: Emotional Intelligence, Employee Empowerment, Employee Job Satisfaction